An ARDL Co-Integration Approach to Inflation, FDI and Economic Growth in Libya - CAVUSOGLU, Behiye; ALSABR, Mariam (Journal of Advanced Research in Law and Economics, 2018)
Despite the different economic systems that are prevalent around the world, inflation and foreign direct investment (FDI) are two important instruments to attain economic objectives. It is apparent that the inflation rate is an important indicator of the economic performance of any country and this has necessitated the urgent need to measure, study and analyze this phenomenon. FDI is another important factor affecting economic growth, which plays an essential role in the economies of host countries, particularly those that are developing economies, including Libya. The Libyan economy has many characteristics and features that make it attractive to the foreign investors. The main aim of the study is to analyze the relationship between inflation, foreign direct investment and economic growth in Libya. In order to investigate the relationship between the variables, the ARDL Bound test was used along with necessary statistical tests. The obtained results showed that there is a continual correlation between inflation, foreign direct investment and economic growth in Libya. Further observations showed that foreign direct investment policies being implemented by the Libyan government have had an adverse effect on economic growth.